(untitled) (المجلة الدولية للبحوث العلمية, 2024)
This paper aims to explore the Influence of AI on Tourism Development Strategies in Saudi Arabia. This paper employed quantitative research methodology and utilized the survey method to collect data. The survey instrument is designed to address research objectives and questions. The collected survey data was analyzed using (SPSS) software. The target population for this study comprises all employees and managers in the Saudi tourism sector. Since it is not feasible to survey the entire population, a representative sample of 80 participants was selected using a random sampling technique. The study revealed a significant gap in AI adoption and expertise in Saudi Arabia’s tourism sector, with 40% of participants reporting low AI experience. However, there is strong recognition of AI’s potential benefits, with 51.2% believing AI will give Saudi Arabia a competitive advantage in tourism. 48.8% agree AI will contribute significantly to Saudi Vision 2030 goals. Furthermore, a Pearson Chi-Square of (0.007) which is less that (alpha=0.05) indicates that there is a significant influence of AI on Tourism Development Strategies in Saudi Arabia. In conclusion, this research recommends that Saudi Arabia’s tourism sector should adopt a proactive and strategic approach to AI integration. The Ministry of Tourism, in collaboration with key stakeholders, should develop a comprehensive AI roadmap specifically tailored for the tourism industry. This roadmap should prioritize the establishment of AI-focused training programs to upskill the existing workforce and prepare future professionals.